Enforcement of Islam in France: Islamization, Development, and Existence - Ahmad Yani; M. Dahlan M (IAIN Parepare, 2022)
This paper aims to reveal the development of Islam in France with the object of discussion including: (1) the process of Islamization in France, (2) the development of Islam in France, (3) Problems and the existence of Muslims in France. To answer this, it is pursued by using the historical method which includes four stages of work systematically, namely: heuristics, conducting a search of literary sources that are relevant to the study being carried out; source criticism, analyzing sources; interpretation of sources; and historiography or writing of research results. The process of Islamization in France began since the Crusades, namely in the 11th to 13th centuries AD, then the process of Islamization continued in 1830, namely when Muslim immigrants arrived in France. In the following periods the process of Islamization in France was through da'wah and marriage. Muslims continued to experience developments in France from year to year, especially through the da'wah and marriage, so it is estimated that in the following years, the Muslim population in France will experience a quantitatively significant. Along with the development of Islam in France, it also faces quite complicated problems, especially the prohibition of wearing the headscarf for Muslim women. Even so, it appears that Muslims in France today still exist and are able to survive against the situations and conditions that surround them.